WARNINGS LOSS OF MIXED INVASION COWS CAUSED BY FASCIOLA, PARAMFISTOMA AND DYKROTSELIYA - Пономар, С. І.; Кручиненко, О. В. (Scientific Progress & Innovations, 2014)
The results of the impact of mixed infestations caused fasciolas, paramfistoma and dikrotseliya and dairy efficiency of cows. Found that mixed infestation paramfistoma and dikrotseliya and causes significant economic damage to farming, is 860 UAH. During the four months of lactation production of the cows were treatment by trematozol above 276 kg, 10 % albendazol ultra 222 kg compared with cows of the control group. As a result of treatment with albendazole and cows trematozolom 10% prevent economic damage in the economy amounted to 1281,4 UAH.